From publicly available data to business decisions - Schweigert, Jonas (2019)
This study describes the basics of business intelligence, before it explains its standard framework. Subsequently, the paper outlines how Google Maps data can be exploited to create a dashboard in Power BI. Thereby, it applies a modified framework to a case study about venues (businesses, transportation infrastructure, and tourist attractions) in Lisbon, Portugal. Five different analysis are carried out: general KPIs, their correlation, an investigation about popular time as well as heat map and location analysis. This work concludes, that businesses and organizations of all kinds can use this information to identify trends and customer behavior to make data-driven decisions.